The Utilization of ChatGPT: Its Correlation with Self-Regulated Learning among Students of Islamic Education at UIN Raden Intan Lampung - A’yun , Risqiya Qurrota; Azizah, Nurul; Zulfikar, Robi; Ranialini , Nadya; Fauzi, Akbar (WISE Pendidikan Indonesia, 2025)
This study aims to analyze the relationship between the use of ChatGPT and the self-regulated learning of students in the Islamic Education Department (PAI) at UIN Raden Intan Lampung. In line with technological advancements, ChatGPT, an artificial intelligence-based tool, has increasingly been utilized in various academic activities, including supporting independent learning processes. This research employs a quantitative approach using a correlational method, where data is collected through a questionnaire measuring both the frequency of ChatGPT use and the level of students' self-regulated learning. The sample consists of 33 randomly selected PAI students. Data analysis was conducted using Pearson correlation analysis to determine the relationship between the two variables. The results indicate a significant and positive relationship between the use of ChatGPT and students' self-regulated learning, meaning that the more frequently students use ChatGPT, the higher their level of self-regulated learning. These findings highlight the potential of ChatGPT as an effective tool for enhancing students' self-regulated learning in the digital age and provide recommendations for developing technology-based learning strategies in higher education.